Immigrants issue in governance of North-East India: A fait accompli and humanitarian compulsions - Singh, Arun Kumar; Suprita Suman (2016)
The geographical boundaries of the North-Eastern part of India made it vulnerable target for the cross-border illegal immigrants. These immigrants are a severe threat upon the livelihood, environment, and security of the people living in these states. But there is another part of the picture which has been ignored and requires a sensitive and justified analysis. The country, surrounded by the India's North-Eastern front is Bangladesh, which is densely populated and suffering from poverty, unemployment, and illiteracy. The immigrants from Bangladesh are unskilled and majority of them are very poor and jobless persons who are scrapping for livelihood. These immigrants have tendency to increase their population owing to their religious beliefs and raising their numerical strength. Due to these problems, immigration and immigrants have always remained as "illegal immigration" and "illegal immigrants" in Indian context. The present article examines the possibilities whether this 'illegal' word can be made 'legal' through regulatory mechanism in Indian context. These regulations can check their involvement in the legal works, their day-to-day economic and political activities and the hurdles which the Indian economy and polity meet to be more adaptable to these illegal burden of immigrants. - Reproduced.
Keywords: Immigrants - India, North-East; Immigrants